ПРОБЛЕМНІ ПИТАННЯ ЗАБЕЗПЕЧЕННЯ ПРАВ ПІДОЗРЮВАНОГО, ОБВИНУВАЧЕНОГО У КРИМІНАЛЬНОМУ ПРОВАДЖЕННІ - Мартовицька, Олена Василівна (SUPREMANCE OF LAW, 2019)
The article concerns the main tendencies of scientific research on the legal and procedural rights guarantees of the defendant, the suspect at the stage of the pre-trial proceedings. The current and previous law of criminal procedure of Ukraine on the issues considered in the article have been investigated, on the basis of which the comparative analysis has been carried out. The results of the analysis are used to provide improvement proposals for the current law. In addition, the inconsistence between the provisions of the Code of Criminal Procedure of Ukraine and the Law of Ukraine «On the Bar and Practice of Law» in terms of ensuring and enforcement of the right to the defense of the suspect and the defendant has been found out which causes difficulty in law enforcement. Various scientific beliefs as well as practices in the context of the research are analyzed. The authors’ assessment as well as the authors’ contemplation of the considered issues are provided. As a result, it is concluded that despite a certain number of novelties introduced in the Criminal Procedure Code of Ukraine in 2012 on the rights protection improvement of individual participants in the criminal proceedings, some alerting problems remain unsolved, in particular, the ones regarding the protection of rights of the defendant or the suspect at the stage pre-trial investigation in the criminal proceedings. Besides, an inaccuracy in the terminology and the content of certain provisions of the Criminal Procedure Code of Ukraine is identified. The practice of the European Court of Human Rights has been studied resulting in the identification of system violations committed by the law enforcement off cials and courts during the investigation of the criminal proceedings. Specific measures to prevent such violations in the future have been proposed. Specific amendments are proposed to improve the current Criminal Procedure Code of Ukraine. All mentioned aspects are reflected in the study.